A proteomic analysis of acute leukemia cells treated with 9-hydroxyoctadecadienoic acid. Issue 1 (December 2016) - Li, Zhen; Chen, Bohong; Wang, Ping; Li, Xin; Cai, Gaotai; Wei, Wei; Dong, Wenqi
Abstract Background 9s-hydroxy-octadecadienoic acid (9S-HOD), one of the natural products of linoleic acid oxygenation by 15-lipoxygenase (15-LOX), has been found to have anti-tumor properties in vitro and in vivo. The present study therefore investigated whether 9S-HOD affects acute leukemia HL-60 cells. Methods The cytotoxicity of 9S-HOD in HL-60 with or without the presence of fetal bovine serum (FBS) in the culture media was tested using cell viability assays and flow cytometry. To explore the mechanism of its anti-tumor activity by 9S-HOD, we used a proteomic analysis to identify HL-60 cells protein profiles, based on two-dimensional gel electrophoresis (2-DE) and mass spectrometry (MS) identification. Results 9S-HOD exerted cytotoxicity efficacy and induced apoptosis in HL-60 cells, and the cytotoxicity was largely attenuated by the presence of FBS in culture media. The proteomic results revealed that 9S-HOD remarkably altered the abundance of 23 proteins that were involved in mRNA metabolic process, protein binding, DNA replication and apoptosis. Conclusions Our results indicated that 9S-HOD exerts cytotoxicity in HL-60 cells by affecting several pathways.